2017
DOI: 10.1007/s40333-017-0015-5
|View full text |Cite|
|
Sign up to set email alerts
|

Endophytic bacteria associated with endangered plant Ferula sinkiangensis K. M. Shen in an arid land: diversity and plant growth-promoting traits

Abstract: Ferula spp. are traditional medicinal plants found in arid land. Large-scale excavation for extracting bioactive compounds from the plants in arid regions of Xinjiang over the last few years has, however, significantly decreased their distributions. Due to the urgent need for preservation of these plant resources, along with the need of searching for alternative source of the useful metabolites, it is important to screen the endophytic microbial resources associated with the plant Ferula sinkiangensis K. M. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 48 publications
(47 reference statements)
5
33
0
Order By: Relevance
“…Paracoccus is also the only known bacterium that possesses all the components of the mitochondrial respiratory chain and oxidative phosphorylation pathway [83]. Species in this genus were reported to be a common endophyte in Phaseolus vulgaris seeds [84], Ferula sinkiangensis seeds [85] and Arachis hypogaea seeds and sprouts [72], as well as several other crops [86]. Delftia species are seed bacterial endophytes known for their antagonistic activity against several plant pathogens, growthpromotion, and nitrogen-xing properties [87][88][89].…”
Section: Discussionmentioning
confidence: 99%
“…Paracoccus is also the only known bacterium that possesses all the components of the mitochondrial respiratory chain and oxidative phosphorylation pathway [83]. Species in this genus were reported to be a common endophyte in Phaseolus vulgaris seeds [84], Ferula sinkiangensis seeds [85] and Arachis hypogaea seeds and sprouts [72], as well as several other crops [86]. Delftia species are seed bacterial endophytes known for their antagonistic activity against several plant pathogens, growthpromotion, and nitrogen-xing properties [87][88][89].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, endophytic resources of arid land are most likely to possess unique and diverse functions, such as degrading chitin, producing siderophore, encoding antimicrobial and antibiotic biosynthetic genes, because of their high ability to adapt the extremely arid environment (Qin et al, 2009;Cho et al, 2015;Egamberdieva et al, 2016Egamberdieva et al, , 2017cLi et al, 2018). For instance, our research group reported that the vast majority of endophytic isolates from Chinese traditional medicinal plants Ferula sinkiangensis, Glycyrrhiza uralensis, and Ferula songorica in Xinjiang arid land were capable of producing both antifungal and plant growth-promoting traits (Liu et al, 2016(Liu et al, , 2017Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Selvakumar et al, 2008), and Achyranthes aspera L. (Devi et al, 2016), as a result of phosphate solubilization, production of phytohormones and siderophores. Additionally, improvement of seed germination parameters by PGPR has been reported for endangered plants (Galdiano Júnior et al, 2011;Gumiere et al, 2014;Liu et al, 2017). Strategies that involve the use of PGPR could be used as complementary tools in conservation programs of endangered native plants from Robinson Crusoe Island, considering the current critical state of some plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Different reports have demonstrated the utility of inoculation of IAA producing PGPR to increase the germination rate of plants. Thus, the isolation of rhizospheric microorganisms that are capable of producing phytohormones, such as IAA, could potentially be used as biostimulants for improving plant germination and growth rate of the endangered species, as has been shown in other reports (Galdiano Júnior et al, 2011;Gumiere et al, 2014;Liu et al, 2017). Therefore, it was hypothesized that the use of PGPR could improve the rate germination of endangered plants from Robinson Crusoe Island.…”
Section: Introductionmentioning
confidence: 92%